Catalysis by the JmjC histone demethylase KDM4A integrates substrate dynamics, correlated motions and molecular orbital control - Ramanan, R; Chaturvedi, SS; Lehnert, N; Schofield, CJ; Karabencheva-Christova, TG; Christov, CZ (Royal Society of Chemistry, 2020)
The Nε-methyl lysine status of histones is important in the regulation of eukaryotic transcription. The Fe(II) and 2-oxoglutarate (2OG) -dependent JmjC domain enzymes are the largest family of histone Nε-methyl lysine demethylases (KDMs). The human KDM4 subfamily of JmjC KDMs is linked with multiple cancers and some of its members are medicinal chemistry targets. We describe the use of combined molecular dynamics (MD) and Quantum Mechanical/Molecular Mechanical (QM/MM) methods to study the mechanism of KDM4A, which catalyzes demethylation of both tri- and di-methylated forms of histone H3 at K9 and K36. The results show that the oxygen activation at the active site of KDM4A is optimized towards the generation of the reactive Fe(IV)-oxo intermediate. Factors including the substrate binding mode, correlated motions of the protein and histone substrates, and molecular orbital control synergistically contribute to the reactivity of the Fe(IV)-oxo intermediate. In silico substitutions were performed to investigate the roles of residues (Lys241, Tyr177, and Asn290) in substrate orientation. The Lys241Ala substitution abolishes activity due to altered substrate orientation consistent with reported experimental studies. Calculations with a macrocyclic peptide substrate analogue reveal that induced conformational changes/correlated motions in KDM4A are sequence-specific in a manner that influences substrate binding affinity. Second sphere residues, such as Ser288 and Thr289, may contribute to KDM4A catalysis by correlated motions with active site residues. Residues that stabilize key intermediates, and which are predicted to be involved in correlated motions with other residues in the second sphere and beyond, are shown to be different in KDM4A compared to those in another JmjC KDM (PHF8), which acts on H3K9 di- and mono-methylated forms, suggesting that allosteric type inhibition is of interest from the perspective of developing selective JmjC KDM inhibitors.